13.7% Efficiency graphene–gallium arsenide Schottky junction solar cells with a P3HT hole transport layer. (September 2015) - He, Hang; Yu, Xuegong; Wu, Yichao; Mu, Xinhui; Zhu, Haiyan; Yuan, Shuai; Yang, Deren
Abstract: Combination of graphene (Gr) with semiconductor to form heterojunction solar cells has recently attracted significant attention due to its simple process with low cost. Here, we have reported a new structure of graphene–gallium arsenide (Gr–GaAs) solar cells using poly(3-hexylthiophene) (P3HT) as hole transport layer. It is found that the open-circuit voltage ( V oc ) and short-circuit current ( J sc ) of the solar cells get significantly increased due to the introduction of P3HT layer. Initial power conversion efficiency (PCE) of 6.84% can be obtained for the Gr–GaAs solar cell with a P3HT layer. The performance improvement of the Gr–GaAs solar cell with a P3HT layer is strongly associated with its small saturation current, due to the increase of built-in barrier and the reduction of the carrier recombination at the Gr–GaAs interface. By doping Gr via bis(trifluoromethanesulfonyl)-amide (TFSA) and utilizing an efficient TiO2 antireflective film (AR film), the PCE of the solar cell with a P3HT layer can reach a maximum value of 13.7%, which is the highest value achieved for the Gr–GaAs solar cells so far. These results pave a new way for the fabrication of high efficiency Gr–GaAs solar cells. Graphical abstract: A 13.7% efficiency has been achieved for the graphene/gallium arsenide solar cell with P3HT a hole transport layer after doping and application of antireflective film. Highlights: A new structure of Gr–GaAs solar cell using P3HT as hole transport layer has been reported. The performances of Gr–GaAs solar cells get significantly increased due to the introduction of P3HT layer. Initial PCE of 6.84% has been obtained for the Gr–GaAs solar cells. By TFSA doping and antireflective film application, a highest efficiency of 13.7% has been achieved for Gr–GaAs solar cells.